729 Feasibility assessment of integrated road traffic casualties registry in West Bank, Palestine. (1st September 2016) - Baniode, Mohammad; Storozhenkho, Oleg; Salman, Rand
Abstract : Background: Road traffic casualties and risks are poorly quantified in the West Bank, Palestine. The aim of this study was to provide a first-ever overview of road traffic casualties (RTC) surveillance systems, and to assess the feasibility of establishing an integrated RTC registry in West Bank to provide reliable data to decision makers. Methods: General assessment methodology for surveillance systems and registries (World Health Organisation and CDC, USA) were used. The assessment took place in 2014 in collaboration with the Palestinian Ministry of Health (MoH) and Ministry of Interior. Qualitative methods were used, including semi-structured questionnaires, in-depth interviews and review of grey literature. Results: At least five stand-alone surveillance systems operated by different agencies in the West Bank collect data related to road traffic accidents. These systems do not have a common set of indicators, no formal case definitions or standard operating procedures (SOPs). There is a lack of quality assurance systems at all levels. There are large discrepancies in reported casualties: for 2012 the Palestinian Civil Police (PCP) reported 120 fatalities, whereas MoH reported both 34 and 112 from separate sources of data. Privacy concerns hinder some organisations from sharing data. MoH and PCP data are sufficiently complete to support a robust integrated registry. Conclusions: An integrated registry for RTC is feasible. The establishment should comprise a framework for all essential parts of a registry, including stakeholder relations and a comprehensive quality assurance system. Steps toward technical improvement include establishing a multisectoral working group; developing a common set of indicators and case definitions; revising data collection forms and developing SOPs for the whole continuum of data flow.